Bed load tracer mobility in a mixed bedrock/alluvial channel. Issue 4 (6th April 2017) - Ferguson, R. I.; Sharma, B. P.; Hodge, R. A.; Hardy, R. J.; Warburton, J.
Abstract: The presence of bare or partially covered rock in an otherwise alluvial river implies a downstream change in transport capacity relative to supply. Field investigations of this change and what causes it are lacking. We used two sets of magnet‐tagged tracer clasts to investigate bed load transport during the same sequence of floods in fully alluvial, bare rock, and partial‐cover reaches of an upland stream. High‐flow shear stresses in different reaches were calculated by using stage loggers. Tracers seeded in the upstream alluvial channel moved more slowly than elsewhere until the frontrunners reached bare rock and sped up. Tracers seeded on bare rock moved rapidly off it and accumulated just upstream from, and later in, a partial‐cover zone with many boulders. The backwater effect of the boulder‐rich zone is significant in reducing tracer mobility. Tracer movement over full or partial sediment cover was size selective but dispersion over bare rock was not. Along‐channel changes in tracer mobility are interpreted in terms of measured differences in shear stress and estimated differences in threshold stress. Key Points: Tracers dispersed more rapidly over fully exposed bedrock than in reaches with partial sediment cover Tracers were least mobile in the upstream alluvial channel that controls supply to the bedrock segment Dispersion patterns are consistent with measured downstream changes in shear stress and estimated changes in threshold stress